Microtomografia computadorizada e radiografia para análise morfométrica da patela em cadáveres caninos de diferentes massas corporais - Bárbara Silva Okano (2023)
The aim of this study was to study the macro and microstructural characteristics of the canine patella using microtomography and radiography techniques in order to provide necessary information for the future development of a patellar prosthesis. For the patellar measurements, 70 cadavers of adult dogs were used, regardless of breed or sex, with body mass between 1 and 50 kg, without clinical evidence of affection in the patellofemoral joint. Canine cadavers were divided into five body mass groups: G1:1 at 4.99 kg; G2: 5 to 9.99 kg; G3: 10 to 19.99 kg; G4: 20 to 29.99 kg and G5: 30 to 50 kg. After extraction, the patellas were preserved in 20% formalin and were later scanned using a microtomography system (Skyscan 1174v2; Bruker micro-CT, Kontich, Belgium). The images were reconstructed using the NRecon software (Skyscan, Aartselaar, Belgium) and analyzed using the CT ‐ Analyzer software (Ctan, Skyscan, Belgium). Patellar measurements such as length, width in the proximal third, width in the middle third, width in the distal third, thickness in the proximal third, thickness in the middle third and thickness in the distal third were performed. Bone mineral density, bone volume, trabecular porosity, number of trabeculae, separation between trabeculae and trabecular thickness were also performed. Subsequently, the patellas were radiographed in the mediolateral and craniocaudal views. For this, the VMI emitter device (VMI Médica, Brazil) associated with Regius computed radiography model 110 (Konica Minolta, Tokyo, Japan) was used. Patellar measurements such as length, width in the proximal third, width in the middle third, width in the distal third, thickness in the proximal third, thickness in the middle third and thickness in the distal third were performed. Data were presented as mean ± standard error of mean. Differences between groups were analyzed using One-Way ANOVA followed by Tukey's post hoc. To evaluate the relationship between patella measurements and patella length by radiography, Pearson's correlation was used. In general, a relationship between patellar dimensions and body mass of dog cadavers was observed. Patellar measurements showed a strong correlation with the patella length evaluated by radiography. The microstructural measures of cortical bone thickness, cortical and trabecular bone volume, cortical bone mineral density and trabecular bone surface were related to dog size. Under the conditions of this study, it can be concluded that the dimension of the patella varies according to the dog's body mass and that the measurement of the patella length by radiography proved to be very sensitive to estimate the patella dimensions.